Efficiency of drug therapy for coxitis in patients with ankylosing spondylitis according to the data of a 12-month prospective follow-up - A. V. Petrov; V. A. Beloglazov; Yu. O. Shevnina; A. A. Petrov (Научно-практическая ревматология, 2019)
Hip joint (HJ) inflammation in ankylosing spondylitis (AS) is a frequent manifestation and an unfavorable prognostic feature of the disease and it requires total hip arthroplasty in 7–8% of patients. Nonsteroidal anti-inflammatory drugs (NSAIDs), sulfasalazine (SSZ), and tumor necrosis factor-α inhibitors are used to treat AS-associated coxitis. However, the influence of these treatments on the time course of HJ structural changes has not been currently studied.Objective: to estimate the time course of HJ changes clinical, X-ray, and ultrasonographic examination was performed in AS patients receiving various drugs: NSAIDs, SSZ, and adalimumab (ADA) during 12 months.Subjects and methods. Seventy-eight AS patients who had clinical, ultrasonographic, and radiological signs of HJ inflammation were followed up. The patients were divided into three groups: 1) 25 patients who took NSAIDs daily; 2) 26 patients who received NSAIDs and SSZ in a daily dose of 2–3 g; 3) 27 patients who were treated with NSAIDs and subcutaneous injections of ADA 40 mg once every 2 weeks. In addition to conventional clinical and laboratory investigations, all the patients underwent radiography with Bath Ankylosing Spondylitis Radiology HIP Index (BASRI-Hip) estimation and HJ ultrasonography.Results and discussion. In Group 2, 12-month SSZ use led to a reduction in median pain intensity during HJ movements on a visual analog scale (VAS) from 26.1 [13.9; 42.7] to 69.3 [56.8; 79.3] mm (p<0.05), CRP levels from 4.4 [1.5; 6.9] to 15.2 [8.3; 21.8] mg/l (p<0.05), and synovial membrane thickness from 6.7 [5.8; 8.5] to 9.6 [7.9; 11.8] mm (p<0.05) compared to the basic data. In Group 3, ADA administration resulted in pain reduction from 14.2 [5.2; 26.7] to 72.1 [65.3; 89.1] mm (p<0.05), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score based on C-reactive protein (ASDAS-CRP) from 1.7 [1.1; 3.1] and 1.4 [1.1; 2.2] to 7.5 [5.9; 8.6] and 3.1 [2.6; 3.9], respectively (p<0.05), CRP levels from 2.7 [0.2; 5.8] to 24.3 [17.4; 35.9] mg/l (p<0.05), and HJ synovial membrane thickness from 6.3 [5.0; 7.7] to 9.9 [8.1; 12.6] mm (p<0.05). SSZ and ADA did not substantially affect the time course of changes in BASRI-Hip and the process of new osteophyte formation in HJ.Conclusion. The use of SSZ and ADA in the complex treatment of patients with AS-associated coxitis leads to a lower HJ synovitis activity.